The Effects of Splenectomy and Autologous Spleen Transplantation on Complete Blood Count and Cell Morphology in a Porcine Model - Poljičak-Milas, Nina; Vujnović, Anja; Migić, Josipa; Vnuk, Dražen; Kardum, Matko (IntechOpen, 2012)
None